Methods to Study Centrosomes and Cilia in Drosophila - Jana, Swadhin Chandra (2016)
Centrioles and cilia are highly conserved eukaryotic organelles. Drosophila melanogaster is a powerful genetic and cell biology model organism, extensively used to discover underlying mechanisms of centrosome and cilia biogenesis and function. Defects in centrosomes and cilia reduce fertility and affect different sensory functions, such as proprioception, olfaction, and hearing. The fly possesses a large diversity of ciliary structures and assembly modes, such as motile, immotile, and intraflagellar transport (IFT)-independent or IFT-dependent assembly. Moreover, all the diverse ciliated cells harbor centrioles at the base of the cilia, called basal bodies, making the fly an attractive model to better understand the biology of this organelle. This chapter describes protocols to visualize centrosomes and cilia by fluorescence and electron microscopy.